Effect Of Crop Establishment And Weed Control Practices On The Performance Of Rice (Oryza Sativa L.) (Applied Biological Research, 2012)
The present study was undertaken to evaluate the performance of  transplanted rice and direct seeded rice (DSR) as crop establishment  methods under different weed control practices. Transplanting method  proved superior over DSR. Among the weed management practices, butachlor (1.5 kg a.i. ha-1) + almix (4 g a.i. ha-1) proved superior over  other weed management practices with respect to grain yield and yield  attributes. Maximum grain yield weed control efficiency was recorded in  transplanted rice with the application of butachlor @ 1.5 kg a.i. ha-1+  almix @ 4 g a.i. ha-1.
Keywords: Crop establishment methods; herbicides; rice; yield